Advances in Materials Innovations in Half Metallic Heusler Alloys for Structural Magnetic and Energy Spintronic Technologies - Kalay, Ece; Özkul, İskender; Guler, Omer; Canbay, Canan Aksu (My University, 2025)
Half-metallic Heusler alloys are promising materials for spintronic and thermoelectric applications. These alloys exhibit metallic conductivity in one spin direction while acting as insulators in the opposite spin direction, enabling nearly 100% spin polarization. This property is crucial for spintronic devices such as magnetic tunnel junctions (MTJs), magnetic random-access memories, and spin-based transistors. This study investigates the electronic, magnetic, and structural properties of Heusler alloys, focusing on their synthesis methods, atomic ordering, and modelling via density functional theory (DFT). DFT-based calculations serve as a key tool for predicting band structures, spin polarization, and magnetic properties. Additionally, the effects of disorder, strain, and compositional changes on material properties are analysed to explore performance optimization strategies. The potential applications of Heusler alloys in spintronic memory devices, thermoelectric energy conversion, and quantum technologies are also discussed. This work is presented as a review article and systematically compiles and interprets findings from the existing literature to provide a broad understanding of the topic. By integrating theoretical and experimental approaches, this study provides a comprehensive overview of the role of these materials in advanced technological applications.
Keywords: Density functional theory; spintronics; magnetic properties; Heusler alloys; Half-metals